A STUDY OF THE RELATIONSHIP BETWEEN PHYSICAL FITNESS MENTAL FITNESS STRESS MANAGEMENT AND POTENTIAL DEVELOPMENT WITH SPORT SKILLS OF UNIVERSITY ATHLETES - Cruthka, Pornvijak; Cruthka, Chomsupak (Journal of MCU Nakhondhat, 2024)
The objectives of this research were to 1) Study the concerning physical fitness; mental fitness; stress management; potential development and sport skills of University athletes. Furthermore, the researchers study 2) The relationship between physical fitness; mental fitness; stress management and potential development with sport skills of University athletes. This is descriptive research, and used to conceptual framework of physical fitness; mental fitness; stress management; potential development and sport skills of University athletes. The sample was 400 athletes of university using multi-stage sampling method. The instrument used for data collection was questionnaire. Testing for quality, the researchers found that the instruments evinced content validity 0.60 - 1.00, and reliability of physical fitness; mental fitness; stress management; potential development; sport skills and reliability of overall questionnaire at the levels of .917, .909, .919, .780 .941 and .966 respectively. The researchers analyzed the data collected in terms of frequency, percentage, mean and standard deviation. In addition, Pearson product moment correlation coefficient. The researchers found that 1) The opinions concerning behavior to practicum regarding physical fitness, mental fitness, stress management and sport skills of University athletes at a level often. As for potential development at a level every time. 2) The correlational analysis revealed that mental fitness and physical fitness significantly positively correlated with sport skills of University athletes at the low level with the statistical significance at .01 level (r = .644, .643 respectively). The stress management and potential development significantly positively correlated with sport skills of University athletes at the high level with the statistical significance at .01 level (r = .732, .724 respectively).